Establishing the ecological restoration network in Argentina: from Rio1992 to SIACRE2015 - Zuleta, Gustavo Adolfo; Rovere, Adriana E.; Pérez, Daniel; Campanello, Paula Inés; Guida-Johnson, Bárbara; Escartin, Celina Andrea; Dalmasso, Antonio Daniel; Renison, Daniel; Ciano, Nicolas Francisco; Aronson, James (2018)
The development of the science and practice of restoration ecology in Argentina can be divided into three periods. The first was 1992–2004, characterized by isolated restoration efforts, mostly in arid and dry ecosystems, and engaging specific people in the academic, agro‐technological, and private sectors as partially required by national regulations, but also inspired by the 1992 Earth Summit, the 1994 Amendments of the Constitutional Law, and environmental guidelines from investment entities. The second period of 2005–2010 showed significantly greater involvement in international networking and conference contributions. The current period from 2011‐present has witnessed rapid advances and national integration. The country's network Red de Restauración Ecológica de Argentina (REA) was founded in 2012, with seven subnational nodes. In 2014, the 2nd REA symposium was held to determine priority areas for restoration and to generate a National Plan. Public agencies, NGOs and volunteer groups are now actively engaged stakeholders. In 2013 Argentina became a founder member of SIACRE (Sociedad Ibero‐Americana y del Caribe para la Restauración Ecológica) and is organizing SIACRE's 4th international conference (April 2015; Buenos Aires). Restoration ecology in Argentina is ascendant because of long‐term efforts related to strengthening democracy, people initiatives, and strong support from SIACRE, SER (Society for Ecological Restoration), SER‐Europe, and the national networks of Colombia, Brazil, Mexico, and Chile. Moreover, Argentina is now the first country to have updated its Civil Code by integrating the environment as a “legal good,” which reinforces the citizens' rights to demand the implementation of degradation prevention and/or ecosystem restoration measures.